Utilização de ácidos fosfônicos para decoração e crescimento de nanoestruturas - Mariana de Castro Prado (2013)
In this thesis, two-dimensional materials and self-assembled organic systems were investigated, topics of great interest both to nanoscience and nanotechnology. The results illustrate the versatility of the self-assembled layers as alternatives to decorate and promote growth of nanostructures. A combination of microscopy and spectroscopy techniques was employed to characterize the samples and the results were compared to theoretical calculations. The main type of organic molecule used here was linear phosphonic acids, species with a polar headgroup and a linear alkyl chain. It was seen that those molecules form a two-dimensional crystal atop graphene and hexagonal boron nitrite (h-BN). Combining atomic force microscopy (AFM) and first principles calculations, it was demonstrated that these molecular crystals keep registry with graphenes and h-BNs hexagonal lattice. The corrugation of the crystal detected by AFM allows the determination of the substrate (graphene or h-BN) crystallographic orientation without the need of atomic resolution images. Raman spectroscopy data confirmed the theoretical prediction that the molecular crystal induces a well-defined p-type doping on graphene (around 1013 cm-2). Another configuration, graphene atop vertical self-assembled bilayers, was investigated and the measured doping was one order of magnitude smaller. Another work dealt with optimization of graphenes etching condition using AFM, optical microscopy and Raman spectroscopy. The investigated etching techniques, reactive ion etching (RIE) and plasma etching, are two of the most widely employed techniques in device fabrication. It was shown that despite their wide use to keep track of etching process in graphene, optical microscopic and Raman spectroscopy are insensitive to graphenes etching residue and suggest the complete removal of the monolayer before all the material is actually removed. Given that this residue can greatly affect device performance for one-atom-thick materials, it is important to use AFM to calibrate the etching process. The two-dimensional phosphonic acid crystals were used to seed the growth of metal oxides atop graphene using atomic layer deposition (ALD). ALD allows precise control of the thickness of a variety of materials grown on substrates that have reactive groups in the surface that seed the deposition. Graphene and the alkyl chains are inert but the phosphonic moiety is reactive, promoting growth of zinc oxide that keeps the same registry shown by these molecules with the substrate. For aluminum, hafnium and zirconium oxides, the growth disrupts the molecular organization. Phosphonic acid and ZnO layer were characterized with AFM and X-rays photoelectron spectroscopy. They were used as a mask for etching and nanostructured graphene was obtained. The systematic study of etching conditions previously mentioned was employed in the last step of this third work. Finally, the decoration of titanium substrates with phosphonic acids was investigated. Bare and functionalized substrates were immersed in solution containing calcium and phosphorus ions and it was observed that the phosphonic acids increase the deposition of inorganic crystals. These crystals were identified as hydroxyapatite, the main inorganic component of bones. Thus, this could be a fast and inexpensive route to increase metallic implants osseointegration. The characterization of two-dimensional organic crystals atop graphene and h-BN was conducted at Laboratório de Nanoscopia of the Physics Department of UFMG, in collaboration with Electronic Structure and Raman Spectroscopy groups. Hydroxyapatite deposition was also conducted at the same department, in collaboration with INMETROs metrology division. Etching and ALD studies were performed during an internship (between January and December, 2012) at Northwestern University, Materials Science and Engineering Department, Prof. Mark Hersams group.